2018
DOI: 10.1016/j.jsams.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on resilience for military readiness and preparedness: Report of an international military physiology roundtable

Abstract: Modern warfare operations often occur in volatile, uncertain, complex, and ambiguous (VUCA) environments accompanied by physical exertion, cognitive overload, sleep restriction and caloric deprivation. The increasingly fast-paced nature of these operations requires military personnel to demonstrate readiness and resiliency in the face of stressful environments to maintain optimal cognitive and physical performance necessary for success. Resiliency, the capacity to overcome the negative effects of setbacks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 67 publications
0
96
1
8
Order By: Relevance
“…While it has also been suggested that the increase in f R may reflect the metabolic demand of the cognitive task [9], this interpretation is unlikely in light of the notion that metabolic inputs do not play a substantial role in the regulation of f R [11,[19][20][21][22]. Hence, f R is a sensitive marker of the cognitive effort exerted in a task, with important implications for the health and performance of a variety of workers [198][199][200].…”
Section: Current Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…While it has also been suggested that the increase in f R may reflect the metabolic demand of the cognitive task [9], this interpretation is unlikely in light of the notion that metabolic inputs do not play a substantial role in the regulation of f R [11,[19][20][21][22]. Hence, f R is a sensitive marker of the cognitive effort exerted in a task, with important implications for the health and performance of a variety of workers [198][199][200].…”
Section: Current Evidencementioning
confidence: 99%
“…Cognitive load is also common in a variety of workers performing dynamic tasks, including soldiers [200] and healthcare professionals (e.g., nurses) [198]. Contact-based techniques are the best candidates to monitor f R in these workers [24].…”
Section: Measurement and Computingmentioning
confidence: 99%
“…Military personnel are often required to maintain performance while experiencing profound sleep and circadian disturbance, due to rapid travel across time zones and continuous or sustained operations. Sleep restriction and circadian misalignment have negative health, performance, and safety consequences, including reduced effectiveness, efficiency, resilience, and readiness [6,7], a greater risk of motor vehicle crashes and injuries [8], higher rates of posttraumatic stress disorder and risky health behaviors in military personnel [4,9], more safety violations and citizen complaints for police officers [10], and greater risk of metabolic disease and cancer [11,12]. To mitigate these health, performance, and safety risks, a greater understanding of vulnerability to sleep restriction and circadian misalignment is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptive military operations are a hallmark of modern warfare and depend on the capacity for flexible, resilient behavior. Airmen face extreme physical and mental demands that require the capacity to overcome the negative physical and psychological effects of operating in challenging field environments characterized by “volatile, uncertain, complex, and ambiguous” events 1 . A primary aim of research in the nutritional sciences is therefore to establish and validate nutritional interventions for the modern warfighter that are designed to provide optimal nutritional support and supplementation for body and mind.…”
Section: Introductionmentioning
confidence: 99%